2018
DOI: 10.21276/ap.2018.7.2.26
|View full text |Cite
|
Sign up to set email alerts
|

Original article Pharmacokinetic profiles of marbofloxacin following single and repeated oral administration in broiler chickens

Abstract: Marbofloxacin is a synthetic, 3 rd generation floroquinolone compound, having concentration dependent bactericidal activity. After administration of drugs through oral route, first pass effect or pre-systemic elimination is one of the major factors which results in to reduced bioavailability. The present study was planned to investigate the pharmacokinetics of marbofloxacin, following single (5 mg/kg) and repeated dose (5 mg/kg) for 5 days oral administration in broiler chickens. Plasma samples were analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In combination pretreated broiler chickens, lower elimination rate constant () and higher elimination half-life (t 1/2β ) indicated reduced rate of drug elimination from body. Lower t 1/2β of 4.62 ± 0.42 h was reported earlier after single oral administration of marbofloxacin in broiler chickens (Patel et al 2018). In support to our findings, higher values of t 1/2β were recorded after piperine combination with oxy tetracycline (normal: 4.93 ± 0.42 h; piperine treated: 6.38 ± 0.44 h) in hens (Singh et al, 2005) and gatifloxacin (normal: 3.74 ± 0.073 h; piperine treated: 4.03 ± 0.097 h) in layers (Patel et al, 2011).…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…In combination pretreated broiler chickens, lower elimination rate constant () and higher elimination half-life (t 1/2β ) indicated reduced rate of drug elimination from body. Lower t 1/2β of 4.62 ± 0.42 h was reported earlier after single oral administration of marbofloxacin in broiler chickens (Patel et al 2018). In support to our findings, higher values of t 1/2β were recorded after piperine combination with oxy tetracycline (normal: 4.93 ± 0.42 h; piperine treated: 6.38 ± 0.44 h) in hens (Singh et al, 2005) and gatifloxacin (normal: 3.74 ± 0.073 h; piperine treated: 4.03 ± 0.097 h) in layers (Patel et al, 2011).…”
Section: Resultsmentioning
confidence: 43%
“…Mean apparent volume of distribution (Vd (area) /F) in combination pretreated broiler chickens was (2.30 ± 0.27 l/kg) which significantly (p < 0.05) higher than piperine (1.71 ± 0.39 l/kg) and quercetin (1.65 ± 0.26 l/kg) alone groups. Patel et al (2018) has observed lower Vd (area) value of 1.32 ± 0.10 l/kg after oral administration of marbofloxacin in broiler chickens. Piperine and quercetin in combination shown largest volume of distribution suggesting more drug penetration in deeper body tissues as compared to alone pretreatment groups.…”
Section: Resultsmentioning
confidence: 88%
“…The pharmacokinetic profile of marbofloxacin has been extensively studied and investigated in different species of birds viz., in broiler chickens (Atef et al, 2017;Patel et al, 2018), Japanese quails (Aboubakr and Abdelazem, 2015), bilgorajska geese (Anser anser domesticus) (Sartini et al, 2020); ostriches (De Lucas et al, 2005) and blue-gold macaws (Carpenter et al, 2006). The effects of lactic acid pre-treatment on pharmacokinetics of enrofloxacin in Chinese mitten crab (Eriocheir sinensis) (Su et al, 2019) and effects of Lactobacillus acidophilus on pharmacokinetics of marbofloxacin in rats (Birhanu et al, 2017) were reported.…”
Section: Resultsmentioning
confidence: 99%
“…It might led to an increased risk of herbal drug interactions. The piperine alkaloid derived from pepper has been observed to be a potent enhancer of the bioavailability and therapeutic efficacy of the concurrently administered of various antimicrobial agents like beta-lactams, ciprofloxacin, oxytetracycline, norfloxacin, marbofloxacin and ampicillin (Hiwale et al, 2002;Patel et al, 2018). It exhibits a wide variety of biological effects which include; anti-inflammatory, antioxidant, antidepressant and hepatoprotective activity (Lee et al, 2005;Patel and Shah, 2009;Shaul et al, 2018;Bhadarka et al, 2018;Modi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%